2011
DOI: 10.1021/nn102885p
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Blinking and Enhanced Exciton Emission from Individual Carbon Nanotubes

Abstract: Blinking and spectral diffusion are hallmarks of nanoscale light emitters and a challenge for creating stable fluorescent biomarkers or efficient nonclassical light sources. Here, we demonstrate suppression of blinking and spectral diffusion of individual single-wall carbon nanotubes by manipulation of their dielectric environment, resulting in 5-fold enhanced light emission. In addition, it was found that the characteristic slopes of the blinking power laws are largely independent of the dielectric environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 37 publications
7
63
0
Order By: Relevance
“…The fact that doping value maintains in the presence/absence of PMMA indicates that the contact between protruding SiO 2 features and graphene is main contributor to doping and PMMA has negligible effect. Similar trend has been observed in single-walled carbon nanotube (SWNT) [42][43][44]: while SWNT on quartz substrate does not have or weak photoluminescence (PL) [43,45], SWNT embedded in PMMA [44] or on sapphire [45] displays strong PL. This is attributed to significant doping effect of SiO 2 compared to neural PMMA or basic sapphire.…”
Section: Resultssupporting
confidence: 68%
“…The fact that doping value maintains in the presence/absence of PMMA indicates that the contact between protruding SiO 2 features and graphene is main contributor to doping and PMMA has negligible effect. Similar trend has been observed in single-walled carbon nanotube (SWNT) [42][43][44]: while SWNT on quartz substrate does not have or weak photoluminescence (PL) [43,45], SWNT embedded in PMMA [44] or on sapphire [45] displays strong PL. This is attributed to significant doping effect of SiO 2 compared to neural PMMA or basic sapphire.…”
Section: Resultssupporting
confidence: 68%
“…By performing a statistical study on more than 40 SWNTs, we find a FWHM distribution centered around 500 µeV with values as low as 250 µeV (resolution limited). We stress that, despite the lack of control of the microscopic dielectric environment in our sample, the observed FWHM distribution is cen- presented in the literature [20,29,30], or comparable to the values reported in studies focusing on the control of the environment-induced dephasing (air-bridging or polymer wrapped SWNTs) [25,31]. As a reference for CVD-grown SWNTs, we compare typical spectra of L-SWNTs with those of similarly processed CoMoCat SWNTs.…”
supporting
confidence: 75%
“…. ) and extrinsic (residual doping [23], interfacial inhomogeneities [24], fluctuating environment [9,25],. .…”
mentioning
confidence: 99%
“…7 Capping layers were found to reduce blinking on surface nanotubes, presumably because they act as diffusion barriers. 8 Very recently, while this paper was under review, it was reported that elevated laser powers increase stepwise blinking frequency in micelle-encapsulated nanotubes. 9 Also very recently, relatively long (several micrometers) micelle-encapsulated nanotubes in solution have been imaged in photoluminescence while being chemically attacked to induce blinking.…”
Section: Resultsmentioning
confidence: 94%